Effects of transdiagnostic cognitive-behavioral therapy and transcranial electrical stimulation on depression symptoms in patients with panic disorder: CBT in patients with panic disorder - Hadi Ghanavat , Shokouh; Mousavi, Seyed Asghar; Keykhosrovani, Moloud (Chronic Diseases Journal, 2025)
BACKGROUND: Characterized by recurrent panic attacks and a high risk of comorbid anxiety disorders, panic disorder is a chronic and debilitating condition. Despite available treatments, many individuals experience limited response or relapse. This study investigated the potential of transdiagnostic cognitive-behavioral therapy (tCBT) and transcranial electrical stimulation (tES) to reduce depressive symptoms in patients with panic disorder. METHODS: This quasi-experimental study with pretest-posttest and control group investigated patients diagnosed with panic disorder seeking treatment at psychological centers in Ahvaz City, Iran, in 2023. Using convenience sampling, 60 eligible participants were randomly assigned to one of the three groups (n = 20 each): a tCBT group (ten 60-minute sessions), a tES group (ten 20-minute sessions), and a no-intervention control group. The Beck Depression Inventory (BDI) was used for data collection, and analysis of covariance (ANCOVA) was performed using SPSS software. RESULTS: Both tCBT and tES significantly reduced depression symptoms (P < 0.01). However, no statistically significant difference was observed between the tCBT and tES groups in terms of their effectiveness in alleviating depression symptoms in patients with panic disorder. CONCLUSION: This study suggests that both tCBT and tES may be viable treatments for reducing depressive symptoms in individuals with panic disorder. Future research with larger, more diverse samples is warranted to establish the long-term efficacy of these interventions and explore their potential for mitigating cognitive-behavioral comorbidities.